Ultrasonographic Evaluation of the Femoral Cartilage, Achilles Tendon, and Plantar Fascia in Young Women Wearing High‐Heeled Shoes. Issue 6 (7th March 2019) - Mezian, Kamal; Ata, Ayşe M.; Kara, Murat; Şahin Onat, Şule; Gürçay, Eda; Çalışkan, Aslı; Simoes, Maria I.T.; Akıncı, Ayşen; Özçakar, Levent; Franchignoni, Franco
Abstract: Background: Specific attention on the musculoskeletal impact of wearing high‐heeled shoes (HHS) has mainly focused on knee osteoarthritis and the literature is limited to biomechanical changes. The distal femoral cartilage has not been morphologically studied. Additionally, although heel elevation is coupled with a shear stress at the heel and overloaded calf muscles, Achilles tendon (AT) and plantar fascia (PF) thicknesses have not been assessed either. Objective: To investigate whether the distal femoral cartilage, AT, and PF were different in women wearing HHS and flat‐heeled shoes (FHS) and specifically, different in terms of AT/PF and distal femoral cartilage thicknesses. Design: Cross‐sectional observational study. Setting: Tertiary care center. Participants: There were 34 women (mean age; 31.1 ± 6.4, body mass index [BMI]; 21.6 ± 2.4 kg/m 2 ) in the HHS group and 54 women (mean age; 29.5 ± 7.2 years, BMI 22.5 ± 2.9 kg/m 2 ) in the FHS group ( P = .271, P = .102, respectively). Women wearing shoes with a heel height of >5 cm were enrolled in the HHS group, and those wearing shoes with a heel height of <1.4 cm were included in the FHS group. Main Outcome Measurements: Distal femoral cartilage from the lateral condyle, intercondylar area and medial condyle (MFC), AT and PF thicknesses, and any abnormalities were evaluated bilaterally by ultrasound. Results: Within‐group comparisons yielded thicker right MFC ( P = .022) and left AT ( P = .028) only in the HHS group. Between‐group comparisons yielded thicker left AT in the HHS group ( P = .040). PF thicknesses were similar both within and between group comparisons (all P > .05). Right AT thickness was positively correlated with right (r = .469, P = .005) and left (r = .402, P = .018) PF thicknesses only within the HHS group. Only calcaneal irregularity/spur was found to be common in the HHS group ( P = .038). Conclusions: We found thickening of the right MFC and left AT in those wearing HHS, whereas PF thickness was not significantly different between those wearing HHS and those wearing FHS. Level of Evidence: III